Comparison of laparoscopic gastropexy performed via intracorporeal suturing with knotless unidirectional barbed suture using a needle driver versus a roticulated endoscopic suturing device: 30 cases. Issue 7 (16th September 2017) - Coleman, Kristin A.; Monnet, Eric
Abstract: Objective: To compare two suturing techniques for prophylactic laparoscopic gastropexy in healthy dogs. Study design: Retrospective case series. Animals: Thirty healthy client‐owned dogs from breeds predisposed to gastric dilation volvulus. Methods: Medical records of dogs presented for prophylactic laparoscopic gastropexy performed with knotless unidirectional barbed suture were reviewed. Dogs were grouped based on the device used for suturing, consisting of an endoscopic needle driver (END) vs an endoscopic suturing device (ESD). Signalment, weight, surgery time, number of suture bites per side of gastropexy, and intraoperative complications were compared between groups. Results: The END group consisted of 10 dogs, with a median age of 1.09 years (range 0.5‐2.67), weight of 41.5 kg (range 25‐66), surgical time of 49.5 minutes (range 35‐77), and a median of 5 suture bites per side (range 4‐6). The ESD group included 20 dogs, with a median age of 1.75 years (range 0.6‐8.75, P  = .0944), weight was 37.5 kg (range 20‐62, P  = .5823), surgical time of 55 minutes (range 30‐76, P  = .808), and a median of 6 suture bites for the first side (range 4‐7, P  = .072) and 7 for the second side (range 4‐8, P  = .003). No major complications and no conversion to open celiotomy occured in either group. Minor complications occurred in 3 dogs in the ESD group, all related to device dysfunction and suture breakage. Conclusion: Laparoscopic gastropexy may be performed effectively with either of these suturing techniques.